An In Vitro Evaluation of Periotest Implant Stability Measurements Taken on Implant Retained Crowns and Healing Abutments - Cianna O'Brien; David Naughton; Bahman Honari; Lewis Winning; Ioannis Polyzois (Wiley, 2024)
ABSTRACT Objective To assess the reliability of implant stability measurements recorded with the Periotest device and to investigate the differences in values when these measurements were taken on implant retained crowns and healing abutments. Materials and Methods Fifty‐six implants in eight synthetic bone blocks were used to carry out implant stability measurements using the Periotest device by two different operators. Each block constituted an example of bone of density D1, D2, D3, or D4, and two blocks of each density were used. The healing abutments placed were of a height to allow approximately 6 mm of the implant‐abutment complex to be supracrestal and temporary crowns were made to match the dimensions of an average central incisor. Descriptive statistics were used to describe the perio test values (PTVs) at each of the different heights on the implant abutments and implant crowns. Means for each site were calculated and distribution of data assessed using the Kruskal Wallis test. The interclass correlation coefficient (ICC) was used to determine the relationship between the PTVs recorded on the implant abutments and implant crowns. Results The mean PTV (±standard devidation) recorded across all sites was 5.57 ± 11.643 on the implant abutments, and 12.27 ± 11.735 on the temporary crowns. Excellent/good inter‐operator ICCs were recorded for the mid‐abutment site in all bone blocks D1-D4 (ICC = 0.814, p < 0.001, ICC = 0.922, p < 0.001, ICC = 0.938, p < 0.001, ICC = 776, p < 0.001). For mid crown sites, ICC between operators was excellent/good only for recordings in D2 bone (ICC = 0.897, p < 0.001). Conclusions Periotest device seems to be able to reliably measure implant stability across all types of bones when the implant stability is assessed at approximately 3 mm coronal to the implant platform for abutments and 4.5 mm for implant supported single crowns.